Avaliação clínica, laboratorial e anatopatológica do sistema urinário de ovinos confinados com e sem suplementação de cloreto de amônio - Santarosa, Bianca Paola [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The incidence of urolithiasis is high in sheep raising, especially in males raised under intensive management. The urinary acidification with ammonium chloride is an effective method to prevent this disease. The objectives of this study with feedlot lambs getting concentrated diet with high protein content, supplemented or not with ammonium chloride, were to verify the effect of diet fed in confinement, rich in concentrated on the formation of uroliths and development of urolithiasis; analyzing the macroscopic and histopathological characteristics of the urinary system; relate the clinical findings, laboratory tests of renal function (urea and creatinine) and necropsy in the presence of uroliths. It was used 60 male sheep, crossbred Ile de France X White Dorper, three to four months old, randomly divided into two groups: Group I (n=40) received 400 mg/kg of ammonium chroride/animal/day orally, for 42 consecutive days; Group II (n=20) was not treated with ammonium chloride. The diet consisted of 85% concentrate, 15% hay, mineral salt and water ad libitum. Moments (M) for clinical evaluation and collection of blood for measurement of serum urea and creatinine were determined as M0, immediately prior to the beginning of the experiment and at intervals of seven days in moments M1, M2, M3, M4, M5 and M6, totaling 56 days of confinement. After the confinement period, the animals were sacrificed, necropsy was performed and their urinary systems were collected for macroscopic and microscopic examination. The animals were observed daily throughout the experimental period, but no animal showed symptoms of obstructive urolithiasis. The values of serum creatinine concentration were below the standard of normality and the values of urea remained above it. Microcalculus were found in the renal pelvis of five animals in both groups. In addition, other changes were found, such as congestion of the renal medullary region and hydronephrosis. The ...

Na ovinocultura, a incidência da urolitíase é elevada, principalmente em machos criados sob manejo intensivo. A acidificação urinária com cloreto de amônio é um método eficiente para prevenção dessa doença. Os objetivos deste estudo com ovinos confinados recebendo dieta concentrada com elevado teor proteico, suplementados ou não com cloreto de amônio, foram: verificar o efeito da dieta fornecida no confinamento, rica em concentrado, sobre a formação de urólitos e desenvolvimento de urolitíase obstrutiva; analisar as características macroscópicas e histopatológicas do sistema urinário; relacionar os achados clínicos, os exames laboratoriais de função renal (ureia e creatinina) e necroscópicos com a presença de urólitos. Utilizaram-se 60 ovinos machos, mestiços Ile de France X White Dorper, com três a quatro meses de idade, distribuídos aleatoriamente em dois grupos: Grupo I (n=40), que recebeu 400mg/kg de cloreto de amônio/animal/dia, por via oral, por 42 dias consecutivos; Grupo II (n=20), não tratado com cloreto de amônio. A alimentação constituiu-se de 85% de concentrado, 15% de feno, sal mineral e água à vontade. Momentos (M) de avaliação clínica e colheita de sangue para dosagem sérica de ureia e creatinina foram determinados como: M0, imediatamente antes do início do experimento e em intervalos de sete dias nos momentos M1; M2; M3; M4; M5 e M6, totalizando 56 dias de confinamento. Após o período de confinamento, os animais foram sacrificados, realizou-se necropsia e o sistema urinário foi colhido para exame macro e microscópico. Os animais foram observados diariamente para verificar a incidência de urolitíase nos dois grupos, durante todo o período experimental, porém nenhum animal apresentou sintomatologia de urolitíase obstrutiva. Os valores da concentração sérica de creatinina estiveram abaixo e os valores de ureia ficaram acima do padrão de normalidade para a espécie. Encontram-se...
Clinical, laboratory and anatomopathological evaluation of the urinary system of feedlot sheep wit and without ammonium chloride supplementation
Keywords: Aparelho urinário - Cálculos; Calculos (Patologia); Ovino - Doenças; Amonio; Histopatologia veterinaria